Comparative metagenomic study unveils new insights on bacterial communities in two pine-feeding Ips beetles (Coleoptera: Curculionidae: Scolytinae) - Khara, Arunabha; Chakraborty, Amrita; Modlinger, Roman; Synek, Jiří; Roy, Amit (Frontiers in Microbiology, 2024)
Climate change has recently boosted the severity and frequency of pine bark beetle attacks. The bacterial community associated with these beetles acts as "hidden players", enhancing their ability to infest and thrive on defence-rich pine trees. There is limited understanding of the environmental acquisition of these hidden players and their life stage-specific association with different pine-feeding bark beetles. There is inadequate knowledge on novel bacterial introduction to pine trees after the beetle infestation. Hence, we conducted the first comparative bacterial metabarcoding study revealing the bacterial communities in the pine trees before and after beetle feeding and in different life stages of two dominant pine-feeding bark beetles, namely Ips sexdentatus and Ips acuminatus. We also evaluated the bacterial association between wild and lab-bred beetles to measure the deviation due to inhabiting a controlled environment.Significant differences in bacterial amplicon sequence variance (ASVs) abundance existed among different life stages within and between the pine beetles. However, Pseudomonas, Serratia, Pseudoxanthomonas, Taibaiella, and Acinetobacter served as core bacteria. Interestingly, I. sexdentatus larvae correspond to significantly higher bacterial diversity and community richness and evenness compared to other developmental stages, while I. acuminatus adults displayed higher bacterial richness with no significant variation in the diversity and evenness between the life stages. Both wild and lab-bred I. sexdentatus beetles showed a prevalence of the bacterial family Pseudomonadaceae. In addition, wild I. sexdentatus showed dominance of Yersiniaceae, whereas Erwiniaceae was abundant in lab-bred beetles. Alternatively, Acidobacteriaceae, Corynebacteriaceae, and Microbacteriaceae were highly abundant bacterial families in lab-bred, whereas Chitinophagaceae and Microbacteriaceae were highly abundant in wild I. accuminatus.We validated the relative abundances of selected bacterial taxa estimated by metagenomic sequencing with quantitative PCR.Our study sheds new insights into bacterial associations in pine beetles under the influence of various drivers such as environment, host, and life stages. We documented that lab-breeding considerably influences beetle bacterial community assembly. Furthermore, beetle feeding alters bacteriome at the microhabitat level.Nevertheless, our study revisited pine-feeding bark beetle symbiosis under the influence of different drivers and revealed intriguing insight into bacterial community assembly, facilitating future functional studies.